2016
DOI: 10.1002/mawe.201600521
|View full text |Cite
|
Sign up to set email alerts
|

Method of determination of enthalpy and entropy for the technology of laser cutting

Abstract: This paper is devoted to the mechanisms of laser cutting of material from the point of view of thermodynamics. Thanks to the special properties of a laser beam, lasers have proved to be a reliable tool for the industry. Scientific databases currently include many papers devoted to scientific and engineering research aimed at the development and application of the technology of lasers. Operating costs of a laser system are high when operated inefficiently, therefore efficient operation is quite desirable. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Weng et al [16] found that the increase in laser power would increase the porosity and interface cracking sensitivity of the cladding layer. M. Harničárová et al [17] studied the mechanisms of laser cutting of material from the point of view of thermodynamics, and created an analytical expression of the thermo-dynamic parameters of the cut, which can be used both for predictions concerning the technology process, as well as for control of the process. Ovisk et al [18] studied the thermal energy influence on various types of construction steels during laser beam cutting, and verified how the thermal energy influences the surface layer of material during laser cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Weng et al [16] found that the increase in laser power would increase the porosity and interface cracking sensitivity of the cladding layer. M. Harničárová et al [17] studied the mechanisms of laser cutting of material from the point of view of thermodynamics, and created an analytical expression of the thermo-dynamic parameters of the cut, which can be used both for predictions concerning the technology process, as well as for control of the process. Ovisk et al [18] studied the thermal energy influence on various types of construction steels during laser beam cutting, and verified how the thermal energy influences the surface layer of material during laser cutting.…”
Section: Introductionmentioning
confidence: 99%